2020
DOI: 10.1101/2020.05.02.070680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mitotic protein NuMA plays a spindle-independent role in nuclear formation and mechanics

Abstract: Eukaryotic cells typically form a single, round nucleus after mitosis, and failures to do so can compromise genomic integrity. How mammalian cells form such a nucleus remains incompletely understood. NuMA is a spindle protein whose disruption results in nuclear fragmentation. What role NuMA plays in nuclear integrity, or whether its perceived role stems from its spindle function, is unclear. Here, we use live imaging to demonstrate that NuMA plays a spindle-independent role in forming a single, round nucleus. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…On the other hand, the interphase role of the N-terminal region of NuMA is not clear. Although both N-terminal and C-terminal globular domains contain several S/TPXX motifs which are supposed to contribute to DNA binding ( Suzuki, 1989 ), the N-terminal NuMA fragments do not show clear DNA or chromatin binding compared to NuMA’s C-terminal ( Serra-Marques et al, 2020 ). However, the N-terminal domain may contribute to the lattice formation of NuMA oligomers in the nucleus ( Gueth-Hallonet et al, 1998 ; Harborth et al, 1999 ), as described below.…”
Section: Dynein-binding Domains In the N-terminal Region Of Numamentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the interphase role of the N-terminal region of NuMA is not clear. Although both N-terminal and C-terminal globular domains contain several S/TPXX motifs which are supposed to contribute to DNA binding ( Suzuki, 1989 ), the N-terminal NuMA fragments do not show clear DNA or chromatin binding compared to NuMA’s C-terminal ( Serra-Marques et al, 2020 ). However, the N-terminal domain may contribute to the lattice formation of NuMA oligomers in the nucleus ( Gueth-Hallonet et al, 1998 ; Harborth et al, 1999 ), as described below.…”
Section: Dynein-binding Domains In the N-terminal Region Of Numamentioning
confidence: 99%
“…Recently, Serra-Marques et al (2020) found that the long coiled-coil is also required for the formation of a single, round nucleus, and that this role is independent from NuMA’s role in spindle formation. In addition, the authors revealed that a small portion of the coiled-coil 213–705 is sufficient to prevent NuMA’s C-terminal region from binding chromosomes during late metaphase and anaphase ( Serra-Marques et al, 2020 ).…”
Section: The Central Long Coiled-coil Domain Of Numamentioning
confidence: 99%
See 3 more Smart Citations